Penggunaan Tayangan Video Sebagai Media Pembelajaran Pada Massa Pandemic Covid 19 di Madrasah Aliyah Persiapan Negeri Besitang - Wahyu Ziaulhaq (Formosa Journal of Sustainable Research, 2022)
This study describes the use of video shows as a medium of learning for the mass of the COVID-19 pandemic at Madrasah Aliyah, the preparation of the state of Besitang. The purpose of this research is to educate readers that during the COVID-19 pandemic, learning activities are not carried out face-to-face but use video shows to break the chain of transmission of Covid 19, then the video shows are watched by students at home and students are given assignments by the teacher. The research method used is qualitative. The approach used is an anthropological and sociological approach. Data collection techniques are through observation and unstructured interviews, after the data is obtained, the data is analyzed scientifically. The results of the research that have been found indicate that first, video shows are the right media to be used as a source of teaching materials for the masses of covid 19 so that students can study at home through the video. Second, video shows are packaged in language that is easily understood by students with a duration of around thirty minutes. Third, video shows are packaged with an attractive display that contains teaching material content.